ANALISIS MESIN PRODUKSI UNTUK MENINGKATKAN KINERJA DENGAN METODE OVERALL EQUIPMENT EFFECTIVENESS (OEE) - Supriyati, Supriyati; Wiyatno, Tri Ngudi; Hadikristanto, Wahyu; Rusdianto, Imam (Heuristic, 2024)
PT. Hankook Tire Indonesia is a company operating in the manufacturing sector that produces vehicle tires. In the production process, the downtime that occurred during the last year was 1050.18 hours and the highest downtime occurred in the mixing machine at 524.45 hours. This downtime resulted in the production process only reaching an average of 80% of the set target. Seeing the problems experienced by PT. Hankook Tire Indonesia, it is necessary to carry out research to measure the performance of mixing machines using the OEE method and analyze losses using the Six Big Losses method. Based on the results of the performance analysis, the mixing machine is not running ideally with an OEE value of 66%. After analyzing with Six Big Loss, the biggest loss that causes engine performance to decrease is Speed ​​Losses with a percentage of 80%. The main cause of losses due to Speed ​​Losses is the Dust Collector. After analyzing the root of the problem with fishbone and recommending improvements with 5W+1H, it was able to increase the performance of the mixing machine to ideal performance with an OEE value after improvement of 91%.